Equivalence Challenges in Machine Translation: An Analysis of Google Translate Output through Mona Baker's Theory (2011) and Post-Editing Strategies - Marhamah; Hidayati, Dini; Prasatyo, Bayu Andika (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This research aims to analyse the level of equality based on Mona Baker's theory translated by J.K. Rowling's "Harry Potter and the Order of the Phoenix" from English to Indonesian using Google Translate. Specific goals include identifying and discussing translation issues at various linguistic levels and providing post-editing suggestions for machine-translated output. The methodology section outlines the qualitative research design, using observation and document methods for data collection. The data source is J.K. Rowling's novel, translated by Google Translate into Indonesian. The process includes observing, identifying, classifying, and evaluating the level of equivalence in the translated text. In conclusion, this introduction provides the basis for an in-depth analysis of the degree of translation equivalence in the context of machine translation, especially in the translation of literary works such as "Harry Potter and the Order of the Phoenix". the analysis of translation problems in the Harry Potter novel reveals common challenges across different parts of sentences, categorized into word level, above word level, textual level, grammatical level, and pragmatic level. While machine translators assist in translating text, especially with large volumes, they still require human monitoring for post-editing to rectify inaccuracies. Consistency in translation practice is emphasized to improve student abilities and ensure progress. Teachers are urged to apply consistent practices, progressing from simple to complex texts and allowing students freedom in choosing translation materials once professional.